Multiphase PdCu nanoparticles with improved C1 selectivity in ethanol oxidation. Issue 18 (27th July 2022) - Xu, Wenxia; Wu, Xueke; Yuan, Yueyue; Qin, Yingnan; Liu, Yanru; Wang, Zuochao; Zhang, Dan; Li, Hongdong; Lai, Jianping; Wang, Lei
Abstract : PdCu/CNT-300 catalysts with a mixed crystalline phase were successfully prepared. The introduction of Cu elements and the presence of a phase interface in the mixed phase facilitated electron transfer and increased the rate of the EOR. Abstract : Here, a mixed crystalline catalyst with face-centered cubic (fcc) and body-centered cubic (bcc) phases and its application in the oxidation of ethanol in alkaline medium are reported. PdCu nanoparticles were synthesized in an oil bath, followed by carbon nanotube loading. With the different calcination temperatures, PdCu/CNT nanoparticles produce the fcc crystal phase, bcc crystal phase and mixed crystal phase of fcc and bcc. A mixed crystalline phase of fcc :  bcc = 2 : 1 appears at a calcination temperature of 300 °C; PdCu/CNT-300 has the highest electrocatalytic activity of ethanol oxidation, the mass activity reaches 7.8 A mgPd −1 and the area activity reaches 17.0 mA cm −2, and it has good electrochemical stability and structural stability. In addition, the selectivity of the C1 pathway can reach 53.9%. This excellent performance is attributed to the enhancement of the electron-donor activity of Pd by Cu, realizing the synergistic effect between the bimetals, and the phase interface brought by the mixed crystal phase, which together tune the electronic structure of the catalyst and promote the electron transfer rate of the catalyst. This ultimately improves the CO resistance of the catalyst and enhances the C–C bond-breaking ability of the catalyst, which in turn improves the selectivity of the C1 pathway for the oxidation of ethanol in alkaline media and improves the catalytic oxidation performance of ethanol.